LESSONS ON THE ROLE OF THE US STATE IN TECHNOLOGICAL DEVELOPMENT AND INNOVATION - Nguyen Hong Nga (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
This paper highlights the need for increased involvement of the Vietnamese government in technological innovation and development to achieve sustainable growth. Using the United States as precedent in forming technological cores and foundations (i) Defense Advanced Research Projects Agency (DARPA); (ii) Small Business Innovation Research Program (SBIR); (iii) Cethromycin; (iv) Nanotechnology. The author concludes and offers seven suggestions to boost the process of technological innovation and development in Vietnam. Code: 23020801